Risk factors for peripherally inserted central catheter malposition in preterm infants: a multicenter retrospective study - Liang, Chunyan; Liu, Jinming; Tang, Yingzi; Zhao, Wenpiao; Xin, Ruining; Gu, Xiaoqun; Huang, Fang; Lai, Yu'e; Huang, Wangjin; Liu, Yanhong; Lin, Mei; Pan, Lili; et al. (Frontiers in Pediatrics, 2025)
ObjectiveTo explore the risk factors affecting peripherally inserted central catheter (PICC) tip malposition in preterm infants.MethodsA retrospective collection of clinical data from preterm infants who underwent PICC placement in the neonatal departments of Guangxi Maternal and Child Health Hospital and eight other hospitals from January 2021 to April 2024 was conducted. The incidence of catheter tip malposition was analyzed. The infants were divided into two groups based on the occurrence of catheter tip malposition: the malposition group and the non-malposition group. Multifactorial logistic regression and multimodel logistic regression analyses were employed to explore the influencing factors of PICC tip malposition in preterm infants.ResultsA total of 1,449 infants were ultimately included in the study, with an incidence of catheter tip displacement of 12.56% (182 out of 1,449). Adjusted results from multimodel regression analysis of covariates indicated that Sample selection location in Guilin (OR = 2.30, 95% CI:1.24∼4.25), Yulin (OR = 4.35, 95% CI: 2.27∼8.34) and Qinzhou (OR = 2.63, 95% CI:1.37∼5.08), duration of catheter insertion procedure (OR = 1.01, 95% CI: 1.01∼1.02), duration of catheter dwell (OR = 1.04, 95% CI: 1.02∼1.07), weight percentile at the time of catheter malpositioning (OR = 11.39, 95% CI:4.81∼26.95), extremely preterm group (<28 weeks gestation) (OR = 4.42, 95% CI: 1.29∼15.16) were risk factors for catheter tip displacement. Additionally, site of PICC catheterization in neck as a risk factor (OR = 3.48, 95% CI: 1.89∼6.40).ConclusionSample selection location in Guilin, Yulin and Qinzhou, duration of catheter insertion procedure, duration of catheter dwell, weight percentile at catheter removal, extremely preterm group (<28 weeks gestation) and site of PICC catheterization in neck may increase the risk of PICC catheter tip malposition.